The Benefits of Developing EFL Materials Using L1 Culture A Case study of the 1st year students of Ammar Thlidji University in Laghouat - Benfareh ,Halima; Guesmi, Mostapha (Faculty of Letters and Foreign Languages Department of English, 2019)
Teaching foreign culture has been recently receiving much attention and focus in the fields of second/foreign language teaching. This dissertation is concerned with the importance of using mother culture in EFL materials. In addition, the paper points out the idea of learner’s own space where he creates his own meanings of the two languages’ cultures (C1 and C2). This work focuses on students’ questionnaire that shed lights on their attitudes towards learning English and foreign culture using learners’ L1 culture (mother culture). The results obtained reveal that first year students of English Language and literature in the Department of English at Ammar Thlidji University of Laghouat need to know more about their mother cultural background, and believe that Algerian history is good enough to acquire English culture. As further recommendations, Minister of Education should submit a unified program for teaching Mother Cultures in EFL process at the university level